(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
Digitalization of learning applies technology in the learning process, one of which is by developing augmented reality (AR) media. The use of technology in learning has been proven effective in increasing students’ motivation and conceptual understanding. The developed ’DIOS_AR’ media is expected to solve problems in improving students’ conceptual understanding of the water cycle by providing more meaningful learning and attracting student participation. The study was conducted on 5th grade students at Al Falah Darussalam 2 Elementary School, Sidoarjo using the 4D research and development model (Define, Design, Develop, and Disseminate). Data collection was carried out by interviews, observations, tests, and questionnaires. From the data obtained from the media validator, the media was very feasible with a percentage of 92%, and the test score obtained N-Gain 73.17 was categorized as high and effective so that the DIOS_AR media could increase student engagement, attract their attention, and improve their conceptual understanding of water cycle learning.